PERAN PET (HEWAN PELIHARAAN) PADA TINGKAT STRES PEGAWAI PURNATUGAS - Risa Juliadilla; S.Candra Hastuti H. (Jurnal Psikologi Integratif, 2018)
In gerontology, the issue of pets as a "negative effect killer during retirement" has long been believed to be an activity that can improve living welfare. This study used 77 male retired employees. This study aims to determine the effect of pet ownership on stress levels, differences in stress levels between groups that have animals and do not have animals and know the characteristics of the group of pet owners related to stress levels. The research data will be analyzed using simple regression, Mann Whitney test and Chi square. The research instruments used were the Perceived Stress Scale from Cohen (1988) and the questionnaire. Obtained overall results of respondents at moderate stress levels. The research findings are that pet ownership has an effect on stress levels of 37, 2%. It was also found that groups that had pets had lower stress levels than those who did not have pets. In addition, it was concluded that there was a correlation between the level of education and the level of stress that was not significant, the correlation between marital status and residence status with stress levels significantly. Keywords: :Pet, Retirement, Stress Levels